Distribution and tritrophic associations of aphid parasitoids of tribes Ephedrini and Praini (Aphidiinae: Braconidae: Hymenoptera) in India - Rajendra Singh (Journal of Fauna Biodiversity, 2025)
The members of tribes Ephedrini and Praini (Aphidiinae: Braconidae: Hymenoptera) are exclusively koinobiont aphid parasitoids. Both tribes are widely distributed and some species have been successfully used in biological control of the aphids worldwide. The Ephedrini comprises of 29 species and Praini consists of 16 species of parasitoids in India; parasitising 94 and 79 species in 11 and 13 states/union territories of India, respectively. Among the Ephedrini, Toxares deltiger and Ephedrus plagiator are highly polyphagous, parasitising 27 and 22 species of aphids infesting 28 and 52 host plants with 285 and 110 tritrophic associations, respectively. Among aphid species, Myzus persicae infests38 species of food plants in 8 states/union territories of India. It serves as a host for Ephedrini parasitoids followed by Aphis gossypii and Uroleucon sonchi, parasitised by 8 species each of Ephedrini on 17 and 4 species of host plants in 6 and 3 states/union territories of India, respectively. The Indian fauna of Praini includes only one genus, Praon, of which 5 species are endemic. Praon volucre is highly polyphagous, parasitises 21 species of aphids infesting 27 species of host plants followed by Praon abjectum (10 species of aphids, 13 species of host plants), Praon dorsale (9 species of aphids, 10 species of host plants), Praon orientale (5 species of aphids, 5 species of host plants), and others with 1-4 aphid hosts feeding on 1-4 species of host plants. Jammu & Kashmir hosts a maximum of 11 species of Praon parasitising 34 species of aphids infesting 32 species of food plants followed by Meghalaya (7 species of parasitoids parasitising 20 species of aphids feeding on 18 species of food plants), Uttarakhand (6 species of parasitoids parasitising 8 species of aphids feeding on 6 species of food plants), West Bengal (5 species of parasitoids parasitising 11 species of aphids feeding on 11 species of food plants), Himachal Pradesh (5 species of parasitoids of 7 species of aphids feeding on 9 species of food plants) and other states 1-4 species of parasitoids, parasitising 1-6 species of aphids infesting 1-7 species of host plants. The parasitoids of both tribes are almost distributed in the northeast (Arunachal Pradesh, Manipur, Meghalaya, Mizoram, Nagaland, Sikkim and West Bengal) to the northwest (Himachal Pradesh, Jammu & Kashmir, Uttarakhand) India. Almost two-thirds of Ephedrini and Praini species are recorded in Meghalaya and Jammu & Kashmir, respectively. A detailed tritrophic associations of different genera of Ephedrini and Praini are discussed.